Analysis of OCT1, OCT2 and OCT3 gene polymorphisms among type 2 diabetes mellitus subjects in Indian ethnicity, Malaysia - Al-Ashoor, Sabah Ghasan Abood; Ramachandran, Vasudevan; Inche Mat, Liyana Najwa; Mohamad, Nur Afiqah; Mohamed, Mohd Hazmi; Wan Sulaiman, Wan Aliaa (Elsevier, 2021)
Background: Type 2 Diabetes mellitus (T2DM) is a chronic metabolic disorder. It is a major non-communicable disease affecting 463 million people globally in 2019 and is expected to be double to about 700 million by 2045. The majority are Asians with Indian ethnicity in Malaysia reported as the highest prevalence of T2DM. Cardiovascular disease, renal failure, blindness and neuropathy, as well as premature death are the known morbidity and mortality resulted from T2DM. T2DM is characterized by the dysfunctional insulin physiology that causes reduction of glucose transport into the cells which lead to hyperglycaemia. Hence, one of the important treatments is an oral antidiabetic drug that lowers the serum glucose level in patients with T2DM. This drug will be transported across cell membranes by organic cation transporters (OCT). Therefore, it is important to identify the OCT candidate gene polymorphisms related to T2DM especially among the Indian ethnicity in Malaysia. Methods: Blood samples were collected from 132 T2DM patients and 133 controls. Genotyping of OCT1 (rs628031), OCT2 (rs145450955), OCT3 (rs3088442 and rs2292334) was performed using (PCR-RFLP). Results: No association was observed for genotypic and allelic distributions in all the gene polymorphisms of OCT genes (P > 0.05). However, a logistic regression analysis stratified by gender in a dominant model showed a significant difference for OCT3 among males with T2DM (P = 0.006). Significant association was also observed for OCT3 when stratified to subjects aged > 45 years old (P = 0.009). Conclusion: Based on these findings, the association of OCT3 (rs2292334) could be considered as a possible genetic risk factor for the development of T2DM among Indian males alone.